In vivo contact biomechanics in the trapeziometacarpal joint using finite deformation biphasic theory and mathematical modelling. Issue 2 (February 2016) - Dourthe, Benjamin; D'Agostino, Priscilla; Stockmans, Filip; Kerkhof, Faes; Vereecke, Evie
Highlights: A mathematical model to predict contact biomechanics in the TMC joint is proposed. The trapezium displays a slightly smaller projected contact area than the MC1. Power grasp elicits high intra-articular contact stresses in the TMC joint. Lateral key pinch seems to create higher joint instability. The volar/radial region of the TMC joint is subjected to the highest stresses. Abstract: The assessment of the contact biomechanics in the trapeziometacarpal (TMC) joint during functional tasks represents a relevant way to obtain a better understanding of the onset of osteoarthritis (OA). CT scans of the hand region of 20 female volunteers were taken in relaxed neutral, lateral key pinch and power grasp configuration. 3D models of the first metacarpal (MC1) and the trapezium were created. The articular area of each bone was quantified and a mathematical model was developed in Matlab to evaluate the projected contact area and stress distribution of each bone. The articular areas of the MC1 and the trapezium presented no significant difference. A slightly smaller projected contact area was calculated for the trapezium compared to the MC1. Similar amounts of stress were reported in the neutral and lateral pinch configurations. The highest stress levels were observed during power grasp. Very consistent results for high stress location on the volar/radial articular sub-region were found in the neutral and power grasp configurations. More variation was reported during lateral pinch. The mathematical model presented in this paper offers the possibility to predict contact patterns within the TMC joint based on in vivo CT images.